Pendidikan dalam Perspektif Sejarah: Analisis Perkembangan Sistem Pendidikan di Berbagai Peradaban - Widodo (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This article aims to analyze the development of education systems in various civilizations from a historical perspective, focusing on how education developed and was influenced by social, cultural, political, and economic conditions in each period so that policy makers and society in general can design a better future for education. This research uses the historical method with a focus on collecting, analyzing, and interpreting historical sources relevant to the development of education systems in various civilizations. Researchers will explore archives, manuscripts, documents and other historical evidence to trace how education systems developed in the context of a particular time and place. The results show that although there are variations in educational approaches between civilizations, there are similarities in the role of education as a tool to maintain and expand power, as well as to adapt to social and technological change. The education system also reflects the social hierarchy that existed at the time, where access to education was often limited to certain elites or classes. It is hoped that this research will bring an understanding of the history of education essential for developing a more inclusive and adaptive education system in the present, taking into account the historical legacies that shape current educational patterns.